2007
DOI: 10.3727/154427207783948838
|View full text |Cite
|
Sign up to set email alerts
|

Exposing the Tourist Value Proposition of Zoos and Aquaria

Abstract: The world's urban population has few opportunities for contact with real wild nature and little chance to develop a connection with nature in everyday life. To redress this problem in Western culture, major urban zoos are attempting to bridge the deficit in nature experience by constructing more simulated nature experiences as part of the animal viewing opportunity. The tourist value proposition in urban zoos, however, may not be in the simulated experience of artificial nature, but in the very real and authe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In this hypothesis, human dependence on nature goes beyond a physical dependence, and also includes aesthetic, intellectual, cognitive and spiritual satisfaction (Kellert, 1993). This hypothesis has been widely applied, for example in interpreting the health benefits that come from connecting with nature (Maller, Townsend, Pryor, Brown, & St Leger, 2006), children's responses to pets and the natural world (Fawcett & Gullone, 2001;Kahn, 1997), and the enjoyment people gain from visits to the zoo (Fraser, Gruber, & Condon, 2007). This whole area concerning our relationships with and attitudes towards animals constitutes a field of study usually referred to as Human-Animal Studies, which "explores the spaces that animals occupy in human social and cultural worlds and the interactions humans have with them" (de Mello, 2012).…”
mentioning
confidence: 99%
“…In this hypothesis, human dependence on nature goes beyond a physical dependence, and also includes aesthetic, intellectual, cognitive and spiritual satisfaction (Kellert, 1993). This hypothesis has been widely applied, for example in interpreting the health benefits that come from connecting with nature (Maller, Townsend, Pryor, Brown, & St Leger, 2006), children's responses to pets and the natural world (Fawcett & Gullone, 2001;Kahn, 1997), and the enjoyment people gain from visits to the zoo (Fraser, Gruber, & Condon, 2007). This whole area concerning our relationships with and attitudes towards animals constitutes a field of study usually referred to as Human-Animal Studies, which "explores the spaces that animals occupy in human social and cultural worlds and the interactions humans have with them" (de Mello, 2012).…”
mentioning
confidence: 99%
“…For example, Clayton, Fraser, and Burgess (2011) found zoo visitors' environmental identity and connection to an animal were positively correlated with an interest in conservation. Other studies have documented increases in visitor awareness, empathy, and knowledge following zoo-based interpretation (Fraser, Gruber, & Condon, 2007;Gwynne, 2007;Woods, 2002). Other research has shown mixed results as to the efficacy of interpretive experiences influencing behaviors, and the overall likelihood of visitors adopting pro-conservation behaviors (Smith, Broad, & Weiler, 2008;Smith, Weiler, & Ham, 2011).…”
Section: Interpretation and Behavior Changementioning
confidence: 99%
“…Nature-based tourism is varied and does not necessarily imply responsible travel or conservation of the environment (Buckley, Pickering, & Weaver, 2003). Examples of different contexts studied in nature-based tourism from the perspective of an environmentally responsible approach are: a) National parks (Brown et al, 2010;Davenport, Borrie, Freimund, & Manning, 2002;Halpenny, 2010;Puhakka, 2010); b) Zoos (Ballantyne, Packer, Hughes, & Dierking, 2007;Fraser, 2010;Lukas & Ross, 2005;Smith, Ham, & Weiler, 2011;Swanagan, 2000); c) Aquariums (Ballantyne et al, 2007;Fraser, Gruber, & Condon, 2007;Hall, 1992;Kemmerly & Macfarlane, 2009;Mann & Vernon, 2013); d) Wild-life watching (Ballantyne, Packer, & Falk, 2011;Ballantyne, Packer, & Hughes, 2009;Ballantyne, Packer, & Sutherland, 2011;Smith et al, 2011); and e) Heritage places (Brown, 1999;Uriely, Israeli, & Reichel, 2002).…”
Section: Environmentally Responsible Behaviours and Nature-based Tourismmentioning
confidence: 99%